The evolution of criminal liability for causing bankruptcy (pre-20th century) - Ivanenko , Yevhen (Actual problems of law (Aktual’ni problemi pravoznavstva), 2025)
This article explores the historical development of criminal liability for causing bankruptcy in Ukrainian lands, from the times of Kyivan Rus to the beginning of the 20th century. The author conducts a historical and legal analysis of the provisions that regulated this sphere of public relations in the context of various legal traditions and systems. Particular attention is paid to identifying the features of the legal regulation of bankruptcy in "Ruska Pravda," the Lithuanian Statutes, and the legislative acts of the Russian Empire. Turning to historical sources of law, it is necessary to state that most legal norms that regulate liability for acts related to bankruptcy and insolvency fragmentarily and remotely reflect the content of the modern norm of the Criminal Code of Ukraine, only partially correlating with the modern wording of Article 219 of the Criminal Code of Ukraine. For the purpose of in-depth study of the historical context of the formation of the institution of bankruptcy (insolvency), it is advisable to refer to intersectoral legal norms that define the features of the formation and development of this institution. As a result of the research, the author highlights the key trends in the development of bankruptcy legislation, such as differentiation of insolvency depending on the reasons for its occurrence, the strengthening of criminal liability for intentional actions in the field of bankruptcy, the gradual detailing of the elements of criminal offenses, and the formation of competition law. The study of such historical experience is important for understanding modern criminal law and its further improvement, as it primarily allows us to establish the patterns of formation of the elements of a criminal offense provided for in Article 219 of the Criminal Code of Ukraine. The purpose of the article is a historical and legal analysis of the formation and development of criminal liability for causing bankruptcy in Ukrainian lands before the 20th century, taking into account the influence of the legal systems of various states.